Global burden of HPV‐attributable squamous cell carcinoma of the anus in 2020, according to sex and HIV status: A worldwide analysis. Issue 3 (16th September 2022) - Deshmukh, Ashish A.; Damgacioglu, Haluk; Georges, Damien; Sonawane, Kalyani; Ferlay, Jacques; Bray, Freddie; Clifford, Gary M.
Abstract: Squamous cell carcinoma of the anus (SCCA) is caused by HPV, and is elevated in persons living with HIV (PLWHIV). We aimed to estimate sex‐ and HIV‐stratified SCCA burden at a country, regional and global level. Using anal cancer incidence estimates from 185 countries available through GLOBOCAN 2020, and region/country‐specific proportions of SCCA vs non‐SCCA from the Cancer Incidence in Five Continents (CI5) Volume XI database, we estimated country‐ and sex‐specific SCCA incidence. Proportions of SCCA diagnosed in PLWHIV, and attributable to HIV, were calculated using estimates of HIV prevalence (UNAIDS 2019) and relative risk applied to SCCA incidence. Of 30 416 SCCA estimated globally in 2020, two‐thirds occurred in women (19 792) and one‐third among men (10 624). Fifty‐three percent of male SCCA and 65% of female SCCA occurred in countries with a very high Human Development Index (HDI). Twenty‐one percent of the global male SCCA burden occurred in PLWHIV (n = 2203), largely concentrated in North America, Europe and Africa. While, only 3% of global female SCCA burden (n = 561) occurred in PLWHIV, mainly in Africa. The global age‐standardized incidence rate of HIV‐negative SCCA was higher in women (0.55 cases per 100 000) than men (0.28), whereas HIV‐positive SCCA was higher in men (0.07) than women (0.02). HIV prevalence reached >40% in 22 countries for male SCCA and in 10 countries for female SCCA, mostly in Africa. Understanding global SCCA burden by HIV status can inform SCCA prevention programs (through HPV vaccination, screening and HIV control) and help raise awareness to combat the disease. Abstract : What's new? Squamous cell carcinoma of the anus (SCCA) is the most commonly diagnosed anal cancer subtype for which human papillomavirus (HPV) infection is considered a necessary cause and HIV is a major risk factor. Our study examined SCCA incidence and the contribution of HIV to SCCA among men and women at the country, regional and global level. Analyses show that globally two‐third of SSCA cases occur in women, with the majority of those cases in countries with a high Human Development Index. Men had a higher burden of HIV‐positive SCCA. The findings are relevant for advancing SCCA prevention and screening recommendations.